The effectiveness of task-based language teaching to improve students' speaking skills - Morita Panduwangi (Politeknik Negeri Bali, 2021)
This study aims to find out the effectiveness of Task-Based English Teaching (TBLT) to improve college students’ speaking skills. Teaching speaking is considered to be difficult as there are various factors involved, both from the teachers’ part and the students’ as well. TBLT uses authentic sources of teaching materials with tasks as the essence of the teaching instructions. The research was done in a private college in Bogor. Sixty 1st semester-students of non-English department are the subjects of the research. They were divided into two groups: the control group and experimental group. Each group consists of 30 students. The control group was taught using a more conventional method, however the experimental group was taught using Task-based instructions. A pre and post test were administered to both groups to find out the effectiveness of TBLT to improve their speaking skills. The mean scores of pre and post English speaking tests were tabulated using SPSS to identify whether there was a difference in students’ achievement of both groups and whether the difference was significant or not. Questionnaires were also distributed to find out their perspectives towards the English lessons. The results of the tests were supported by the students’ answers in the questionnaires in which all students of the experimental group showed significant improvement in their speaking skills in term of accuracy and fluency. Their perspective after experiencing TBLT in the English lessons also demonstrates a significant change resulting in students’ higher self confidence in speaking.